The Role of Women Religious in Pastoral Ministry - Kusum (Asian Horizons, 2009)
This paper is an attempt to look at the role of women religious in the pastoral ministry. The paper tries to look at pastoral ministry from various angles. From the point of view of the parish and parish activities, and deals with the identity crisis that women religious face due to the generation gap and the changes taking place in the understanding of pastoral ministry in the new era of professionalism, competence and greater awareness of self worth. The paper invites us to approach pastoral ministry in a broader sense and shows the need for women religious to equip themselves to be effective in ministry. There are various roles inside and outside of parishes which women can handle with efficiency, competence and a sense of fulfilment.